2020
DOI: 10.1039/d0cy00289e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and molecular structure of model silica-supported tungsten oxide catalysts for oxidative coupling of methane (OCM)

Abstract: Catalysts with only dispersed phase Na–WO4 sites where Na/W < 2 are slightly less active but significantly more C2 selective than the traditional Na2WO4/SiO2 catalysts that contain a crystalline phase where Na/W = 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
91
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(101 citation statements)
references
References 47 publications
7
91
1
2
Order By: Relevance
“…For both the fresh dehydrated (Before OCM) and OCM activated (After OCM) supported 5Na 2 WO 4 /SiO 2 catalysts two major reduction regions are present (red and blue shaded areas in Figure 1 b). It was previously reported that the low temperature reduction (red shaded area) corresponds to reduction of surface Na‐WO x sites and the high temperature reduction (blue shaded area) is from the reduction of the Na 2 WO 4 phase [14a] . The relative intensity of red to blue shaded areas significantly increased after activation of the catalyst in the OCM reaction environment.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…For both the fresh dehydrated (Before OCM) and OCM activated (After OCM) supported 5Na 2 WO 4 /SiO 2 catalysts two major reduction regions are present (red and blue shaded areas in Figure 1 b). It was previously reported that the low temperature reduction (red shaded area) corresponds to reduction of surface Na‐WO x sites and the high temperature reduction (blue shaded area) is from the reduction of the Na 2 WO 4 phase [14a] . The relative intensity of red to blue shaded areas significantly increased after activation of the catalyst in the OCM reaction environment.…”
Section: Resultsmentioning
confidence: 87%
“…TAP pump‐probe experiments were conducted over 0.5 Na‐5 WO x /SiO 2 (possessing only surface Na‐WO x sites, [10, 14a] see Figure S1) and 5 Na 2 WO 4 /SiO 2 (containing both surface Na‐WO x sites and molten Na 2 WO 4 phase) catalysts in order to determine the catalytic contributions of the two types of tungstates to the OCM reaction, see Figure 2. In these experiments, pump pulse (O 2 ) and probe pulse ( 13 CH 4 , C 2 H 6 or C 2 H 4 ) were introduced into the catalyst bed with 2 s time delay and the product formation was recorded coincident to the injection of the secondary probe pulse.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dispersed phase catalysts offer key advantages over catalysts containing a mixture of dispersed and crystalline phases 16,[20][21][22][23] since dispersed phase catalysts consist of atomically dispersed sites with the well-defined and molecular and electronic structure that are modifiable via the addition of promoters. Such control of the nature and structure of catalytic active sites remains challenging in the presence of a crystalline phase in supported mixed phase catalysts, which exhibits an ensemble distribution of the active sites and complicating structure-activity analysis.…”
mentioning
confidence: 99%
“…While dispersed phase tri-metal oxide catalysts, i.e., containing all three metal oxides (W, Na, Mn), have not been studied to date, the structure-activity relationships of active sites in dispersed phase bi-metal oxide catalysts (Na-WO x /SiO 2 , Mn-WO x /SiO 2 ) for OCM have been recently reported. 22,25 It was shown that the distorted surface WO 4 sites are present at elevated temperatures (673 K) on the amorphous SiO 2 surface in unpromoted, supported WO x /SiO 2 catalysts. 22 Upon Na-promotion, the extent of distortion of the WO 4 surface site diminishes.…”
mentioning
confidence: 99%